Late Cretaceous and Cenozoic mammals of North America : biostratigraphy and geochronology - Woodburne, Michael O. (Columbia University Press, 2004)
"This book places into modern context the information by which North American mammalian paleontologists recognize, divide, calibrate, and discuss intervals of mammalian evlution known as North American Land Mammal Ages. It incorporates new information on the systematic biology of the fossil record and utilizes the many recent advances in geochronologic methods and their results." "The book describes the increasingly highly resolved stratigraphy into which all available temporally significant data and applications are integrated. Extensive temporal coverage includes the Lancian part of the Late Cretaceous, and geographical coverage includes information from Mexico, an integral part of the North American fauna, past and present."--Jacket